DAMPAK PERCERAIAN DALAM RUMAH TANGGA BAGI PSIKIS ANAK DI DESA DAMAKAWAN KECAMATAN GANDAPURA KABUPATEN BIREUEN ACEH - M.Iqbal; Fazila, Rika (LPPM IAI Almuslim Aceh, 2023)
This research aims to reveal the psychological impact of divorce on children. This type of research is qualitative using library and field methods. Research findings indicate: First, the impact of divorce, which has many negative effects on children's psychological development, can affect all aspects of children's psychological development, starting from intellectual aspects, social aspects, language aspects, moral and religious aspects. Therefore, it can be minimized with various efforts from both parties who have divorced. Starting from strengthening children's spirituality, both before and after divorce. This can make children have strong personalities, understand Islamic law and be able to control themselves according to the provisions of the law. Second, communicate well with children, chat, discuss and help solve the problems the children are facing. Third, pay attention to the living environment in which the child lives after divorce, whether at the father's or mother's house, at his grandmother's house, at school and in his play environment. By giving them attention and opportunities to interact well, express their opinions and take part in various daily activities.